(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Co-Operative Bank is a main rural bank in Kerala. In closing six years the Bank is stepped forward in the manner of deposits, borrowings, and so forth. In this junction, the researcher interest to understand what is the branding strategy and strategies used by the COSMOS BANK. This studies enables to different rural banks are getting right guidelines for his or her future steps. The COSMOS BANK is achieved unique popularity award in DCCB Category- Banking Frontiers 2016 and in 2018, the Bank got award from KSCB for Issue of most RuPay ATM Cards – Banking Frontiers. This achievements are primarily based its branding ideas and unique advertising strategic techniques. In this have a look at like to conclude, the COSMOS BANK financial institution is a role version for different rural bank and its want to develop the agricultural clients in the manner of credit money usages, getting better enterprise ideas and so. In particular, the premise for decision making on the purchase of a bank product depends at the specifics of the work accomplished by using the patron’s responsibilities. The industrial banks of our united states of america must keep in mind the reasons for the decision making and the approaches to the acquisition of financial institution products with the aid of customers at some stage in the improvement of advertising strategies for banking merchandise.